On-The-Fly Kinetics of the Hydrogen Abstraction by Hydroperoxyl Radical: An Application of the Reaction Class Transition State Theory - Baradyn, Maciej; Ratkiewicz, Artur (Frontiers in Chemistry, 2022)
A Reaction Class Transition State Theory (RC-TST) is applied to calculate thermal rate constants for hydrogen abstraction by ∙OOH radical from alkanes in the temperature range of 300-2500K. The rate constants for the reference reaction C2H6 + ∙OOH → ∙C2H5 + H2O2, is obtained with the Canonical Variational Transition State Theory (CVT) augmented with the Small Curvature Tunneling (SCT) correction. The necessary parameters were obtained from M06-2X/aug-cc-pVTZ data for a training set of 24 reactions. Depending on the approximation employed, only the reaction energy or no additional parameters are needed to predict the RC-TST rates for other class representatives. Although each of the reactions can in principle be investigated at higher levels of theory, the approach provides nearly equally reliable rate constant at a fraction of the cost needed for larger and higher level calculations. The systematic error is smaller than 50% in comparison with high level computations. Satisfactory agreement with literature data, augmented by the lack of necessity of tedious and time consuming transition state calculations, facilitates seamless application of the proposed methodology to the Automated Reaction Mechanism Generators (ARMGs) programs.